Effects of substrate on the germination and seedling growth of Quercus suber L. - Kholkhal, Djamel; Benmahioul, Benamar (Biodiversity: Research and Conservation, 2021)
The seedling quality is one of the most important factors for the success of reforestation programs. In this sense, this work aimed to evaluate the effects of substrate on the germination of cork oak acorns from El Aouana forest, located in the Jijel region of north-eastern Algeria, and on the performance of seedlings, particularly their growth. The experiment was performed in the nursery of the Tlemcen Forest Conservation. For this purpose, five substrates were used: S1 (sand), S2 (topsoil), S3 (potting soil), S4 (1/2 sand + 1/2 topsoil) and S5 (1/3 sand + 1/3 topsoil + 1/3 potting soil). Germination and survival rates, and seedling morphological traits: average height of seedlings, average root collar diameter, stem height/root collar diameter ratio (H/D), average number of leaves per plant, leaf length, leaf width and leaf area, were evaluated. Results obtained after 16 months of monitoring in the nursery showed high germination rates of 91.4%, with an average survival rate of 89.5%, and significant differences were recorded between the substrates tested. In terms of growth, the best results were obtained with the potting soil substrate (S3) for all parameters. The lowest yields were recorded in seedlings grown on sand alone (S1).